ERROR ON THE USE OF PAST TENSE IN NARRATIVE TEXT MADE BY ELEVENTH GRADE OF SMK SWASTA BNKP DARO-DARO BALAEKHA - Daya, Etason (Research on English Language Education, 2023)
Grammar is the rules of a language governing the sounds, words, sentences, and other elements, as well as their combination and interpretation. In grammar, there is tense in English which must we know, they were past tense, present tense, future tense, and past future. But here, there are still many students made errors in using past tense of narrative text. This research was aimed to analysic the Error on The Use of Past Tense in Narrative Text Made by Eleventh Grade Of SMK Swasta BNKP Daro-Daro Balaekha. This research designed by using qualitative descriptive method. In analyzing the data, the research used theory of Miles and Huberman; data reduction, data display, and conclusion drawing/verification.the data was documentation, worksheet and interview. The data source of this study was taken from the eleventh grade students of SMK Swasta BNKP Dara-Daro Balaekha. The data of this study are students ‘errors in use past tense. To examine the credibility of this study the researcher used triangulation. The results of this study there are 7 students not mastering the pattern. Then, students difficult to differentiate the use of verbs in sentence are 7, do not have any dictionary are 2 and other reasons limited of vocabulary are 2. The students stated that their teacher usually only give the books rare explain about how to use past tense. From the result of the research, researcher concluded that students conduct errors because of not mastering the pattern of past tense. Suggestion for teacher, students and next researcher expect the result of this research can be benefit for all the sources in scientific work especially.